2017
DOI: 10.3233/jad-161086
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Ginkgolide B Attenuates Amyloid-β1-42 Induced Oxidative Damage and Altered Cellular Responses in Human Neuroblastoma SH-SY5Y Cells

Abstract: Oxidative stress is an upsurge in reactive oxygen/nitrogen species (ROS/RNS), which aggravates damage to cellular components viz. lipids, proteins, and nucleic acids resulting in impaired cellular functions and neurological pathologies including Alzheimer's disease (AD). In the present study, we have examined amyloid-β (Aβ)-induced oxidative stress responses, a major cause for AD, in the undifferentiated and differentiated human neuroblastoma SH-SY5Y cells. Aβ1-42-induced oxidative damage was evaluated on lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 73 publications
0
35
0
Order By: Relevance
“…We observed an alteration in cell morphology, as well as an increase in NeuN levels (a marker for mature neurons) after RA treatment, as previously reported (Cheung et al, ; Lopes et al, ). Various studies have described the characteristics of differentiated cells, and they seem to be an appropriate model to study Aβ peptide‐induced toxicity (Bang et al, ; da Rocha, da Cruz e Silva, & Vieira, 2015; Gill, Kaur, Kaur, Dhiman, & Mantha, ). Here we have used Aβ 25–35 peptide, which has similar toxic effects with respect to cell death, as well as on cell signaling pathway, as the Aβ 1–42 in in vitro models (Frozza et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We observed an alteration in cell morphology, as well as an increase in NeuN levels (a marker for mature neurons) after RA treatment, as previously reported (Cheung et al, ; Lopes et al, ). Various studies have described the characteristics of differentiated cells, and they seem to be an appropriate model to study Aβ peptide‐induced toxicity (Bang et al, ; da Rocha, da Cruz e Silva, & Vieira, 2015; Gill, Kaur, Kaur, Dhiman, & Mantha, ). Here we have used Aβ 25–35 peptide, which has similar toxic effects with respect to cell death, as well as on cell signaling pathway, as the Aβ 1–42 in in vitro models (Frozza et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…GB, a major monomer of extracts from leaves of Ginkgo biloba traditionally used in Chinese herbal medicine, displays a wide range of biological activities, including anti-inflammatory and anti-oxidant effects (26). It has been reported that GB could exert neuroprotective effects against cerebral ischemia/reperfusion injury (CI/RI) via suppressing inflammatory response and scavenging oxygen free radical (27, 28). Both MI/RI and CI/RI are hypoxic and anoxic diseases, which have similar characteristics in pathogenesis and treatment, suggesting that GB may possess a potential value in the treatment strategy of MI/RI.…”
Section: Discussionmentioning
confidence: 99%
“…The 8‐hydroxydeoxyguanosine (8‐OHdG) levels were determined using an enzyme‐linked immunosorbent assay kit (Cloud‐Clone, Katy, TX, USA) (Gill, Kaur, Kaur, Dhiman, & Mantha, 2017). Supernatants were collected from the differentially treated cells and subjected to the assay according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%